Implementation of the TPM-Lean Manufacturing Methodology to Improve the Overall Equipment Effectiveness (OEE) of Spare Parts Production at a Metalworking Company - Canahua Apaza, Nohemy Miriam (2021)
This article intends to demonstrate the feasibility of applying the TPM-Lean Manufacturing methodology in SME manufacturers of metal spare parts, as there is a growth in demand, visible in the sector, which cannot be exploited due to its Overall Equipment Effectiveness (OEE) low values. The aim is to contribute to a better knowledge of the application technique to reduce waste in process industries so that, through an analysis of their production data, the problems that prevent companies from being efficient are identified and, through the selection, development and implementation of the techniques of the Lean Manufacturing Methodology, SME can be oriented to carry out improvement actions in their production systems at a low cost.